IBM PARENTING BAGI GURU DAN ORANG TUA PAUD DI KELURAHAN PUDAK PAYUNG SEMARANG - Retnaningdyastuti .; Tri Hartini; Agung Prasetyo; Venty .; Qoriati Mushafanah (E-Dimas: Jurnal Pengabdian kepada Masyarakat, 2015)
Abstract Science and technology program for the community (IbM) aims to provide teachers and parents knowledges and skills in educating early childhood, especially in the form of parenting and child counseling. The methods used in the implementation of community service activities on developing character of early childhood through modeling and and habituation in the form of counseling and mentoring, such as playing games involving both parents and children. The result shows that the implementation of early childhood education has good responses from the participants. Through habituation and modeling given by teachers/ educators and parents, the activities can convey moral messages to children. Hopefully the children can be developed to have intelligent and healthy personality, and virtuous character. Keywords: early childhood education, parenting, and child counseling